Performance of Distance Learning Compared with Face to Face Learning - Karzan Wakil; Aram Abdulfaraj; Abbas Sadula; Dashne Tofiq; Lezan Nawzad (Journal of Educational Science and Technology (EST), 2019)
This study aims to addresses the gap between the philosophy of distance learning and FTF learning among primary schools. Additionally, this research also aims to compare the student learning outcomes using distance and face-to-face (FTF) in statistics courses. To test the validity of the outcomes, we select three schools in Sulaimani city/ Iraq. The population of the research was selected in the seventh and tenth graders, two groups for each grade were determined for the research.  For the FTF teaching method, direct lectures in the computer lab were presented to the students. While, for the distance learning method, the online course was introduced to via Skype. At the end of each teaching course, a text exam was performed for both groups. The results showed that students passing rate in the exam using FTF was 91% and 83% in Sarchya and Kareem Zand basic school respectively compared to only 67% for online classes in both schools in seventh graders. While for tenth grades in Bakrajo Industrial High School the passing rate for FTF was 81% and for virtual class 60%. This result shows that the students who did not visit classroom performed poorer understanding rate compared to those who attended the class in FTF method